Form, development and function of grass stomata - Nunes, Tiago D. G.; Zhang, Dan; Raissig, Michael Thomas (The plant journal, 2020)
A key challenge for plants is to efficiently use water, particularly when growing in a hot and dry climate. Stomata - cellular breathing pores on leaves that mediate gas exchange between plant and at...
First published: 30 September 2019
Gesehen am 18.01.2021